مساهمة القيادة الاستراتيجية في تحقيق الابداع التنظيمي(دراسة حالة مؤسسة ماما نونا لصناعة البسكويت) - حليمة, حمايتي; مسعود, حنكة (جامعة الوادي university eloued, 2020)
هدفت هذه الدراسة إلى إظهار الدور المتنامي للقيادة الإستراتيجية باعتبارها احد أشكال القيادة المساهمة في تحقيق الإبداع التنظيمي للمؤسسة الاقتصادية، من خلال تحديد الأثر بين أبعاد القيادة الإستراتيجية المتمثلة في ( فلسفة إستراتيجية في العمل، القدرة على التفكير الاستراتيجي، رؤية إستراتيجية في العمل، مهارة اتخاذ القرار الاستراتيجي ) و الإبداع التنظيمي . وذلك بالاعتماد على المنهج الوصفي التحليلي كونه المناسب لموضوع الدراسة، وقد تم جمع المعلومات المتعلقة بالبحث الذي اجري ميدانيا من خلال استبانه و توزيعها على مجتمع الدراسة المتكون من 30 عاملا في مؤسسة ماما نونا المختصة بالبسكويت والتي تشمل فئتين الإداريين و التقنيين و قد تم التحليل بيانات الاستبيان باستخدام برنامج التحليل الإحصائي 25 spss.ومن أهم النتائج التي توصلت إليها الدراسة بعدم وجود علاقة اثر ذات دلالة إحصائية بين القيادة الإستراتيجية و الإبداع التنظيمي عند مستوى معنوية 5%،بالإضافة إلى توفر كل من أبعاد القيادة الإستراتيجية وأبعاد الإبداع التنظيمي بالمؤسسة عند مستوى معنوية 5% كما وضحت النتائج انه لا توجد فروق ذات دلالة إحصائية حول توفر أبعاد القيادة الإستراتيجية بالمؤسسة تعزى للمتغيرات الشخصية ( الجنس،العمر،المستوى التعليمي, الأقدمية) عند مستوى معنوية 5% .وعليه نخلص بأنه واضح للقيادة الإستراتيجية بأبعادها الأربعة لا تؤثر بشكل واضح في تحقيق الإبداع التنظيمي،وان أهمية دورها تكمن في وجود وضوح لرؤية المؤسسة لأفرادها و اهتمام كبير بتأثيرات البيئة الداخلية (نفاذ القوة و الضعف)و البيئة الخارجية (الفرص والتهديدات) وانعكاسها على العمليات الإبداعية داخل المؤسسة وأهم التوصيات : محاولة الاهتمام الكبير بأبعاد القيادة الإستراتيجية لدورها الكبير في تحقيق الإبداع في المؤسسة، التوجيه المستمر لسلوك العاملين و تحفيزهم لتحقيق أهداف المؤسسة في ضوء الرؤية المعمول بها و تطوير مهارات القيادة الإستراتيجية بشكل عام من خلال برامج تدريبية نوعية والعمل على تعزيزها." This study aimed show the growing tole of strategic leadership as one of the forms of leadership in achieving the organizational deposit of the federal institution. By analyzing the impact between the dimensions of strategic leadership represented in (a strategic philosophy at work/ the ability to think strategically /a strategic vision at work/ the skill of strategic decision-making) and regional creativity. Based on the analytical descriptive approach being the appropriate subject of study .the information related to the research that was conducted in the field was collected through is classification and distributed to the study population consisting of 30 workers in the « mama nouna » institution specialized in biscuit .which includes two villas administrative and technicians have analyzed the survey data using the statistical analysis program; 25.one of the ;ost Important findings of the drama in the world is the presence of several statistically significant effect between strategic leadership and organizational creativity. we have an awareness level of 65% .in addition to providing both dimensions of strategic headershipat the level of morale 5% in mama nouna foundation .there sultsalsoshowedthatit has the dimensions of strategic leadership and the dimension of seasonal organizational creativity. at the intestinal level of 55% as the results showed that there are no statistically significant differences regarding the availability of d .the strategic constraint of the institution misattributed to personal expressions (hash .age .educational level .seniority) about us . Moral level 5% .and highisrelated to it and clear to strategic leadership in its four dimensions and clearly affected in Chile hatchingcreativity.And that the importance of its role lies in the presence and explanation of the narration of the institution . its members .and interest in the influences of the internal environmentrheartist .the power and poetry the external environment .joy and appetite –bales) and high reflective of the creative processes within the institution and the most important recommendations and attempt to belong to the great after the leadership of the strategy .the great wall in achieving the human being in an institution .continuous guidance for the behavior of employees and its basis for achieving the goals of a certain amount in force and developing strategic leadership skills in general through quality training programs and honey .."
مذكرة ماستر ادارة اعمال
Keywords: القيادة الإستراتيجية، الإبداع التنظيمي،فلسفة إستراتيجية في العمل، القدرة على التفكير الاستراتيجي، رؤية إستراتيجية في العمل، مهارة اتخاذ القرار الاستراتيجي; strategic leadership: organizational creativity. Strategic philosophy at work. the ability to think strategically. Strategic vision in action. Strategic decisionmakingskill.